Kurukshetra A Symposium on Community Development in India (1952-1955) - The Community Projects Administration, Planning Commission (The Community Projects Administration, Planning Commission, Government of India, 1955)
The Community Development Programme (CDP), launched in post-independence India on October 2, 1952, under the leadership of figures such as Jawaharlal Nehru and inspired by the ideals of Mahatma Gandhi, marked a transformative shift from a centralized administrative model to a participatory framework rooted in aided self-help and grassroots empowerment. Conceived to address the pressing needs of rural India—where the overwhelming majority of the population resided—the programme emphasized integrated development encompassing agriculture, education, health, sanitation, housing, and local governance through revitalized Panchayats and trained Gram Sevaks. Through mechanisms such as the National Extension Service, cooperative societies, leadership camps, and block-level administration, the initiative sought to harmonize government support with community initiative, fostering ownership, self-reliance, and collective responsibility among villagers. Notable experiments, including cooperative brick-kiln industries and village-level agricultural improvements, demonstrated the potential of decentralized planning, voluntary labor, and local resource mobilization to generate both economic growth and social transformation. Despite early achievements in infrastructure creation, agricultural productivity, and community mobilization, evaluations highlighted persistent challenges such as inadequate training of personnel, bureaucratic rigidity, uneven financial expenditure, limited inclusion of women and landless laborers, and the need for deeper ideological clarity in leadership. Ultimately, the programme underscored that sustainable rural development depends not merely on physical targets but on nurturing motivation, cooperative action, responsive leadership, and a renewed community spirit—thereby laying the foundation for a long-term vision of equitable and participatory nation-building in rural India.
Issued by Publications Division on behalf of The Community Projects Administration
Keywords: Community Development Programme; Rural Development; Self-Help Philosophy; Panchayati Raj; Gram Sevaks; Cooperative Societies; Agricultural Modernization; Leadership Transformation; National Extension Service; Women’s Empowerment; Village Infrastructure; Participatory Planning